Platelets and Antiplatelet Medication in COVID-19-Related Thrombotic Complications - Schrottmaier, Waltraud C.; Pirabe, Anita; Pereyra, David; Heber, Stefan; Hackl, Hubert; Schmuckenschlager, Anna; Brunnthaler, Laura; Santol, Jonas; Kammerer, Kerstin; Oosterlee, Justin; Pawelka, Erich; Treiber, Sonja M.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Coronavirus disease 2019 (COVID-19) induces a hyper-coagulatory state that frequently leads to thromboembolic complications. While anticoagulation is associated with reduced mortality, the role of anti-platelet therapy in COVID-19 is less clear. We retrospectively analyzed the effect of anticoagulation and anti-platelet therapy in 578 hospitalized COVID-19 patients and prospectively monitored 110 patients for circulating microthrombi and plasma markers of coagulation in the first week of admission. Moreover, we determined platelet shape change as well as thrombi in post mortem lung biopsies in a subset of COVID-19 patients. We observed no association of anti-platelet therapy with COVID-19 survival. Adverse outcome in COVID-19 was associated with increased activation of the coagulation cascade, while circulating microthrombi did not increase in aggravated disease. This was in line with analysis of post mortem lung biopsies of COVID-19 patients, which revealed generally fibrin(ogen)-rich and platelet-low thrombi. Platelet spreading was normal in severe COVID-19 cases, however plasma from COVID-19 patients mediated an outcome-dependent inhibitory effect on naïve platelets. Anti-platelet medication disproportionally exacerbated this platelet impairment in plasma of patients with fatal outcome. Taken together this study shows that unfavorable outcome in COVID-19 is associated with a profound dysregulation of the coagulation system, whereas the contribution of platelets to thrombotic complications is less clear. Adverse outcome may be associated with impaired platelet function or platelet exhaustion. In line, anti-platelet therapy was not associated with beneficial outcome.